ANALISIS POTENSI DAN STRATEGI PENGEMBANGAN TANAH RUBUH BEACH SEBAGAI DESTINASI WISATA PESISIR BARU DI DESA MALAKU KECAMATAN SERAM UTARA KABUPATEN MALUKU TENGAH - Dwi Partini; Dewilna Helmi (Jurnal Geografi, 2026)
Tanah Rubuh Beach is a newly developed coastal tourism destination located in Malaku Village, North Seram District, Central Maluku Regency. As an emerging destination opened in 2026, this tourism site offers coastal scenery, coral cliffs, ocean waves, gazebos, wooden photo spots, swings, parking areas, and a local ticketing system with an entrance fee of IDR 5,000 per visitor. However, its development still faces several challenges, particularly related to unpaved and rocky access roads, limited supporting facilities, and the need for community-based tourism management. This study aims to analyze the tourism potential and development strategy of Tanah Rubuh Beach as a new coastal destination. The research uses a descriptive qualitative approach with field observation, interviews, documentation, and 4A tourism component analysis, namely attraction, accessibility, amenity, and ancillary services. The results indicate that Tanah Rubuh Beach has strong natural attractions, especially coastal scenery, coral-based landscape, and photo-oriented tourism spaces. Accessibility is relatively strategic because the site is located approximately 200 meters from the main inter-district road, although the internal road still requires improvement. Amenities have started to develop through ticket booths, parking areas, gazebos, swings, and wooden seating areas, but they remain limited in terms of safety, sanitation, and visitor management. The ancillary aspect requires strengthening through institutional support, local community participation, promotion, and coastal risk-sensitive planning. This study recommends that Tanah Rubuh Beach be developed through a community-based and sustainable coastal tourism approach.